Response of agronomic crops to planting date and double‐cropping with wheat. (31st March 2020) - Hare, Andrew T.; Jordan, David L.; Edmisten, Keith L.; Leon, Ramon G.; Post, Angela R.; Vann, Rachel; Dunphy, E. James; Heiniger, Ronnie; Collins, Guy; Washburn, Derek
Abstract: Planting date can affect crop yield and is an important management decision for practitioners. Although wheat ( Triticum aestivum L.) and soybean [ Glycine max (L.) Merr.] can be effectively double‐cropped in North Carolina, if commodity prices and projected economic returns are higher for crops other than soybean, growers might consider a nontraditional, double‐crop system. Direct comparisons of major agronomic crops with different planting dates or in a double‐crop system with wheat are limited in North Carolina. Therefore, research was conducted in North Carolina from 2013 through 2017 to determine yield potential of corn ( Zea mays L.), cotton ( Gossypium hirsutum L.), grain sorghum [ Sorghum bicolor (L.) Moench], peanut ( Arachis hypogaea L.), and soybean planted at two dates within the recommended planting window for full‐season production versus planting these crops after wheat harvest. The experimental design was a split plot, with summer crop serving as the whole plot unit and planting date within a crop serving as the subplot unit. Yield of corn, cotton, grain sorghum, peanut, and soybean in full‐season production exceeded that of double‐cropping with wheat in 5, 5, 2, 4, and 5 yr out of 5 yr of the study, respectively. Estimated economic returns were generated using the 10‐yr average (2008–2017) summer crop prices with the 10‐yr average wheat price. When considering all possible combinations of years and crops (n = 25), in only 20% of the possible combinations was the economic return of the double‐cropping system greater than economic return of full‐season crop production when compared with at least one of the planting dates within the traditional planting window.